2020
DOI: 10.1101/2020.02.12.946780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single Cell Transcriptomics Reveals Dysregulated Cellular and Molecular Networks in a Fragile X Syndrome model

Abstract: Despite advances in understanding the pathophysiology of Fragile X syndrome (FXS), its molecular bases are still poorly understood. Whole brain tissue expression profiles have proved surprisingly uninformative. We applied single cell RNA sequencing to profile a FXS mouse model. We found that FXS results in a highly cell type specific effect and it is strongest among different neuronal types. We detected a downregulation of mRNAs bound by FMRP and this effect is prominent in neurons. Metabolic pathways includin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 112 publications
2
6
0
Order By: Relevance
“…Our small sample size of Fragile X syndrome increases chances that changes in cellular proportion or transcriptional dysregulation may be due to stochastic artifacts. However, replication of past findings including reduced FMR1 expression (Pieretti et al, 1991; Bhattacharyya & Zhao, 2016), increased OPC proportion (Doll et al, 2021), and widespread evidence of metabolic stress (Donnard et al, 2020; Kang et al, 2021), corroborate known molecular neuropathology of the disorder (Licznerski et al, 2020).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Our small sample size of Fragile X syndrome increases chances that changes in cellular proportion or transcriptional dysregulation may be due to stochastic artifacts. However, replication of past findings including reduced FMR1 expression (Pieretti et al, 1991; Bhattacharyya & Zhao, 2016), increased OPC proportion (Doll et al, 2021), and widespread evidence of metabolic stress (Donnard et al, 2020; Kang et al, 2021), corroborate known molecular neuropathology of the disorder (Licznerski et al, 2020).…”
Section: Discussionsupporting
confidence: 62%
“…However, replication of past findings including reduced FMR1 expression (Pieretti et al, 1991;Bhattacharyya & Zhao, 2016), increased OPC proportion (Doll et al, 2021), and widespread evidence of metabolic stress (Donnard et al, 2020;Kang et al, 2021), corroborate known molecular neuropathology of the disorder (Licznerski et al, 2020). Thus, our findings highlight the need for more comprehensive study of Fragile X in human tissue directly in a variety of different cell types.…”
Section: Cellular Proportionmentioning
confidence: 52%
“…Our study shows that in the FK mouse brain cortex, steady state mRNA levels are globally disrupted, which drive the dysregulated translational buffering (Fig 1, 5). FMRP targets are particularly downregulated, which happens specifically in neurons (50). By metabolic labeling and RNA-seq in neurons, we show that the loss of FMRP results in reduced stability not only of its direct target substrates, but also of other mRNAs with an optimal codon bias (Fig 2, 3).…”
Section: Discussionmentioning
confidence: 68%
“…To further refine Ttyh1 expression in NSC subpopulations, we used the published single-cell sequencing data ( Dulken et al, 2017 ; Donnard et al, 2020 ) to analyze Ttyh1 expression in various NSC subtypes by unsupervised clustering analysis ( Figures 2D,E ). The results showed that Ttyh1 was mainly expressed in qNSCs ( Figure 2E ).…”
Section: Resultsmentioning
confidence: 99%